Предмет: Алгебра,
автор: Liliana01
раскрыть выражение в уравнении : (x-2)^2+(x+1)^2-(x-1)(x+1)-14=0
Заранее спасибо
Ответы
Автор ответа:
0
x²-4x+4+(x²+2x+1)-(x²-1)-14=0
x²-4x+4+x²+2x+1-x²+1-14=0
x²-2x-8=0
-8+x²-2x=0
x²-4x+4+x²+2x+1-x²+1-14=0
x²-2x-8=0
-8+x²-2x=0
Автор ответа:
0
Спасибо
Автор ответа:
0
(x-2)^2+(x+1)^2-(x-1)(x+1)-14=0
x^2-4x+4+x^2+2x+1-x^+1 = 14
-2x-8+3x^2 = 0
У меня получилось так.
x^2-4x+4+x^2+2x+1-x^+1 = 14
-2x-8+3x^2 = 0
У меня получилось так.
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Математика,
автор: uncorn567
Предмет: Немецкий язык,
автор: Аноним
Предмет: Биология,
автор: sos8314
Предмет: Математика,
автор: Challeng
Предмет: Математика,
автор: mamin04